The Role of Litigation of the Legal Bureau of Lampung Province Secretariat in Preparing Concept for Handling State Administrative Disputes - Rini Tri Oktavia; Ropi Widyasari (Jurnal Terekam Jejak, 2025)
This paper discusses the role of the Litigation Sub-Division of the Legal Bureau of the Lampung Provincial Secretariat (Sekda Prov. Lampung) in preparing the concept of handling State Administrative disputes, as well as the factors that hinder it. The method used is a normative and empirical legal approach. The author collects data through literature and field studies. Data processing through editing, classification and data systematization methods. The results of the study show that the role of the Litigation of the Legal Bureau of the Lampung Provincial Secretariat in preparing the concept of handling State Administrative disputes has not been implemented optimally. This is because the implementation of duties as the power of attorney of the regional government in the realm of justice is often late, especially in the activities of preparing and submitting power of attorney, answers, duplicates, evidence, witnesses, conclusions.